Case Study of the Opinions to a Sample of Human Resources Working in Duhok Technical Private Institute - Odeesh, James; Saleh, Sami (Humanities Journal of University of Zakho, 2020)
The current research seeks to diagnose the role that green human resource management functions play in promoting blue ocean strategy, through using descriptive analytical method, and to prepared theortical framwork the researchers taken advantage from theoretical literature of the topic, to achieve the research goal, a virtual model was established that clarifies the nature of correlation and impact of research variables represented in green human resource management functions (independent variable) and blue ocean strategy (dependent variable), depending on that, two main hypotheses have been formulated which branched to a number of sub-hypotheses, and by relying on a set of statistical methods, the data collected were tested and analyzed through (44) questionnaires distributed to the employees and teaching staff (research sample) working in Duhok technical private Institute (research community). The most important conclusions was the existence of a significant correlation and impact between the green human resources management functions and blue ocean strategy, while, the most important recommdation was the necessity realizing that strengthening the blue ocean strategy in Duhok technical private Institute requires greater adoption and pay attention to green human resource management functions represented (green recruitment, green training, green performance appraisal, and green compensation).